Evaluation of a lyophilized CRISPR-Cas12 assay for a sensitive, specific, and rapid detection of SARS-CoV-2 - Curti, Lucía Ana; Primost, Ivana; Valla, Sofia; Ibañez Alegre, Daiana; Olguin Perglione, Cecilia; Repizo, Guillermo Daniel; Lara, Julia; Parcerisa, Ivana; Palacios, Antonela; Llases, María Eugenia; Rinflerch, Adriana; Barrios, Melanie; et al. (MDPI, 2021)
We evaluated a lyophilized CRISPR-Cas12 assay for SARS-CoV-2 detection (Lyo-CRISPR SARS-CoV-2 kit) based on reverse transcription, isothermal amplification, and CRISPR-Cas12 reaction. From a total of 210 RNA samples extracted from nasopharyngeal swabs using spin columns, the Lyo-CRISPR SARS-CoV-2 kit detected 105/105 (100%; 95% confidence interval (CI): 96.55–100) positive samples and 104/105 (99.05%; 95% CI: 94.81–99.97) negative samples that were previously tested using commercial RT-qPCR. The estimated overall Kappa index was 0.991, reflecting an almost perfect concordance level between the two diagnostic tests. An initial validation test was also performed on 30 nasopharyngeal samples collected in lysis buffer, in which the Lyo-CRISPR SARS-CoV-2 kit detected 20/21 (95.24%; 95% CI: 76.18–99.88) positive samples and 9/9 (100%; 95% CI: 66.37–100) negative samples. The estimated Kappa index was 0.923, indicating a strong concordance between the test procedures. The Lyo-CRISPR SARS-CoV-2 kit was suitable for detecting a wide range of RT-qPCR-positive samples (cycle threshold range: 11.45–36.90) and dilutions of heat-inactivated virus (range: 2.5–100 copies/µL); no cross-reaction was observed with the other respiratory pathogens tested. We demonstrated that the performance of the Lyo-CRISPR SARS-CoV-2 kit was similar to that of commercial RT-qPCR, as the former was highly sensitive and specific, timesaving (1.5 h), inexpensive, and did not require sophisticated equipment. The use of this kit would reduce the time taken for diagnosis and facilitate molecular diagnosis in low-resource laboratories.